DETERMINING THE FUTURE TRENDS OF HIV PREVALENCE AMONG INDIVIDUALS AGED 15-49 YEARS FOR ZAMBIA USING HOLT’S LINEAR METHOD - Dr. Smartson. P. NYONI; Thabani NYONI (European Science Publishing, 2024)
This study uses annual time series data of HIV prevalence among individuals aged 15-49 years for Zambia from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s linear exponential smoothing model. The optimal values of smoothing constants α and β are 0.9 and 0.1 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15-49 years will continue to decline over the out of sample period but still remain high. Therefore, there is need for a rapid scale up of HIV testing services in the community, strengthening HIV prevention among this age group and improving ART adherence among people living with HIV.
Keywords: Exponential smoothing, Forecasting, HIV prevalence